Exercise addiction and disordered eating in young Lebanese regular sport practitioners: the indirect role of body appreciation and body dysmorphic concerns - Michelle Abi Karam; Rana El Khoury; Carla Hokayem; Nada Akiki; Sahar Obeid; Feten Fekih-Romdhane; Souheil Hallit; Marie Hokayem (Journal of Eating Disorders)
Abstract Background Disordered eating, encompassing behaviors like restrictive dieting, binge eating, and purging, is a prevalent issue with significant psychological and physical consequences. Among athletes, it is often exacerbated by sociocultural pressures and performance demands, making it a critical area of study. Exercise addiction is characterized by compulsive exercise behaviors and is frequently associated with disordered eating; however, the underlying mechanisms of this relationship remain unclear. Limited research has explored the factors that may contribute to the risk of both exercise addiction and disordered eating, particularly in athletes. This study aims to investigate the relationship between exercise addiction and disordered eating in regular sport practitioners and explore the potential indirect roles of body appreciation and body dysmorphic concerns. Examining these constructs is particularly important, as sociocultural pressures and limited mental health resources may uniquely influence their risk factors and experiences. Methods This was a cross-sectional study enrolling 321 Lebanese regular sport practitioners (mean age of 21.09 years with 51.2% males) currently residing in Lebanon.. The questionnaire consisted of four scales, validated in Arabic: the Eating Attitudes Test, the Body Appreciation Scale, Exercise Addiction Inventory—Youth, and the Dysmorphic Concern Questionnaire. Results Body appreciation explained a significant amount of the variance in the association between exercise addiction and disordered eating; higher exercise addiction was significantly associated with lower body appreciation and directly associated with more disordered eating. Moreover, higher body appreciation was significantly associated with less disordered eating. Furthermore, body dysmorphic concerns explained a significant amount of variance in the association between exercise addiction and disordered eating; higher exercise addiction was significantly associated with more body dysmorphic concerns and directly associated with more disordered eating. Additionally, higher body dysmorphic concerns were significantly associated with more disordered eating. Conclusion The study examines the significant indirect role of body dysmorphic concerns and body appreciation between exercise addiction and disordered eating in young adult athletes. These findings underscore the need for interventions targeting body dysmorphic concerns and body appreciation in addressing exercise addiction and disordered eating. By fostering a positive body image and reducing maladaptive behaviors, this can guide coaches and trainers in creating supportive, body positive environments that prioritize athletes’ mental and physical well-being.